Klasifikasi Pengaduan Pelayanan Dispendukcapil Kota Malang Menggunakan Metode Naive Bayes dan Seleksi Fitur Glasgow-II - Choirul Anam; Indriati Indriati; Marji Marji (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The service of each service will never escape from imperfections including the Population and Civil Registry Service (DISPENDUKCAPIL). Service improvement aims to create a sense of comfort and increase satisfaction and trust towards DISPENDUKCAPIL employees for the residents of Malang City. The categories or types of complaints that often go into DISPENDUKCAPIL are complaints on issues of Identity Card (KTP), Family Card (KK), deed (birth, death, and marriage), moving or coming letters. The categorization of various types of service complaints that have been sent to DISPENDUKCAPIL can be done using classification. Classification of service complaints is done using the Naive Bayes method and the Glasgow-II Feature Selection. The process starts from text preprocessing, term weighting, Feature Selection, Naive Bayes training, and Naive Bayes testing. Based on the results of tests conducted using the Naive Bayes method and the Glasgow-II Feature Selection, values ​​of accuracy, precision, recall were 87.5%, 85.1%, 88.075% and an average accuracy of 81.25%. Whereas by using the Naive Bayes method without the Glasgow-II Feature Selection the accuracy, precision, recall values ​​were 84.375%, 83.1%, 81.5625% and the average accuracy was 79.99%. So, that the use of the Naive Bayes method and the Glasgow-II Feature Selection are able to provide better results.